A child with acquired Gerbode defect due to infective endocarditis: Successful percutaneous closure with Nit-occlud device®. (June 2018) - Éden Santos, P.; Villanueva, N.G.; Ballesteros, F.; Matamala-Morillo, M.A.; Zunzunegui, J.L.
Abstract: Left ventricle to right atrial communication, also known as Gerbode defect, is usually a congenital defect and frequently is closed by cardiac surgery. The percutaneous closure has been reported using Amplatzer muscular occluder® I or Amplatzer ductal occluder® II. We report a rare case of a child with an acquired Gerbode defect following Infective Endocarditis of the tricuspid valve which was successfully closed with a Nit-Occlud device®. There are only a few reports of Gerbode defect percutaneously closed using this device, especially in the young pediatric population. Highlights: Acquired Gerbode defect is mostly due to infective endocarditis. Transcatheter device closure of acquired Gerbode defect is a safe treatment. Nit-Occlud® device proved to be another device alternative in the percutaneous treatment. The first case of successful use of Nit-Occlud® device in young children with acquired Gerbode defect patient.